2019
DOI: 10.1136/bcr-2019-230177
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem encephalitis caused by Coxsackie A16 virus in a rituximab-immunosuppressed patient

Abstract: Rituximab and other B cell depleting agents are increasingly used for haematological, immunological and neurological diseases. In a small minority, immunosuppression leads to increased virulence of normally mild infections. Brainstem encephalitis has been described occurring after infection from enteroviruses, more commonly in the paediatric population, but also in immunosuppressed adults. In this paper, we describe an enteroviral brainstem encephalitis in a rituximab-immunosuppressed patient. The enterovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…According to numerous reports, encephalitis has emerged as the most prevalent sequela of enterovirus infection and is typified by neurological symptoms such as vomiting, headache, and convulsions 22–24 . Autopsy of rhesus macaque brains at 30 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to numerous reports, encephalitis has emerged as the most prevalent sequela of enterovirus infection and is typified by neurological symptoms such as vomiting, headache, and convulsions 22–24 . Autopsy of rhesus macaque brains at 30 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…According to numerous reports, encephalitis has emerged as the most prevalent sequela of enterovirus infection and is typified by neurological symptoms such as vomiting, headache, and convulsions. [22][23][24] F I G U R E 5 Viral tissue tropism in coxsackievirus B1 (CVB1)-infected rhesus macaques. (A) Pathological damage and viral antigen expression in the visceral tissues of CVB1-infected rhesus macaques.…”
Section: Suspected Viral Meningitis-like Changes In Cvb1-infected Rhe...mentioning
confidence: 99%
“…The inhibition of the humoral immune response puts the patient at increased risk for viral infections, as evidenced by the black box warnings for reactivation of hepatitis B virus and infection with the John Cunningham (JC) virus [4]. There have been few reported cases of enteroviral meningoencephalitis associated with rituximab, the majority of which occurred in the treatment of hematologic disease [7][8][9][10][11]. A review of the literature indicates that our patient is the first reported case to occur in the treatment of rheumatoid arthritis, the only inflammatory arthritis for which rituximab has an approved indication.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently an evolving recognition of susceptibility to enterovirus among people treated with rituximab, a B cell depleting agent widely used for lymphoma, multiple sclerosis, and systemic lupus erythematosus. [41][42][43][44][45][46][47][48][49][50][51][52][53][54] The population treated with rituximab has generally had a more acute presentation of disseminated disease or meningoencephalitis compared to the slow onset seen in XLA;…”
Section: Diagnosismentioning
confidence: 99%
“…There is currently an evolving recognition of susceptibility to enterovirus among people treated with rituximab, a B cell depleting agent widely used for lymphoma, multiple sclerosis, and systemic lupus erythematosus 41–54 . The population treated with rituximab has generally had a more acute presentation of disseminated disease or meningoencephalitis compared to the slow onset seen in XLA; however, late relapses and late relapses in different organs have been observed suggesting incomplete clearance even in the setting of clinical improvement.…”
Section: Viruses Causing a Distinct Phenotype In Patients With Ieimentioning
confidence: 99%